INSPECTING PRIMARY HEALTHCARE CENTERS IN REMOTE AREAS: FACILITIES, ACTIVITIES, AND FINANCES - Prastuti Soewondo; Meliyanni Johar; Retno Pujisubekti; Halimah Halimah; Dwi Oktiana Irawati (Universitas Airlangga, 2019)
Background: Progress towards health-for-all must be supported by quality health facilities that are available to everyone. However, health care facilities in remote and underdeveloped areas, borderland, and outlying islands or Daerah Terpencil, Tertinggal, Perbatasan dan Kepulauan (DTPK) are facing some constraints to have access to health coverage. Aim: This study aimed to provide a comprehensive picture of the readiness of primary healthcare centers or puskesmas as the main provider of primary health services located in remote areas. Methods: Observations were taken from 18 primary healthcare centers in locations that had been identified by the government as remote and underdeveloped areas, borderland, and outlying islands in 3 provinces: Bengkulu, Nusa Tenggara Timur (East Nusa Tenggara), and South Sulawesi. Results: The findings reveal that many facilities in primary healthcare centers are still insufficient. In particular, roads to primary healthcare centers are in poor physical conditions, operational hours are too short, and doctors and lab technicians are unavailable. The good news is that primary healthcare centers have managed to run many indoor and outdoor activities, such as health education classes and detection of priority diseases in the community. Regarding primary healthcare centers' finances, they largely depend on public funding to support their increasing expenses to provide health services, pay worker salaries, and run indoor and outdoor activities. Conclusions: Overall, some constraints faced by the primary healthcare centers in DTPK include difficult access to facilities and temporary health personnel. All of this information provides valuable inputs to policymakers in building a health infrastructure and human resources for health in DTPK.   Keywords: Remote area, Human resources for health, Primary healthcare center.